ANALISIS SISTEM PENGENDALIAN INTERN ATAS PERSEDIAAN BARANG DAGANGAN PADA PT.PERUSAHAAN PERDAGANGAN INDONESIA - Muhammad Ridwan; Riza Syahputera (Jurnal RATRI (Riset Akuntansi Tridinanti), 2020)
PT. Indonesian Trading Company is a company engaged in the distribution of building materials, fertilizers, pharmaceuticals, and basic necessities to meet the needs of the community. This study uses descriptive qualitative research methods, namely analyzing and describing the application of management control systems to reports on inventory management at PT. Indonesian Trading Company Palembang Branch.The results of the research seen at PT. Indonesian Trading Company is quite effective because the company uses perpetual recording, making it easier for leaders to obtain inventory records in the warehouse. The existence of a clear and structured structure at PT. The Indonesian Trading Company will make the division and implementation of the duties of each section and each work function will minimize data errors on the inventory of goods. Keywords: Distributor of staples, Management Control System, Inventory Management